PROMOSI FILM MENCURI RADEN SALEH DI TWITTER PADA AKUN @mrs_film DAN MINAT MENONTON GENERASI Z - Mulyadi, Iffa Salsabila; Achmad Ismail, Oki (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT Twitter is one of the social media platforms that is not only used to communicate, but also used as a media for delivering information and entertainment in the form of microblogs. Promoting through Twitter gives companies a great opportunity to connect with a large audience to build relationships. Although Twitter is not the social media with the highest number of users in Indonesia, Mencuri Raden Saleh is the first Indonesian movie with the heist genre. Mencuri Raden Saleh Movie actively promotes on Twitter through the official @mrs_film account and the hashtag #MencuriRadenSaleh Movie by utilizing Twitter microblogging. The @mrs_film account is also the account with the most followers among the 15 most watched Indonesian films in 2022. Therefore, this study was conducted to determine how much influence the promotion of the Stealing Raden Saleh Movie on Twitter on the @mrs_film account has on Generation Z's interest in watching. This research uses the SOR Theory (Stimulus-Organism-Response) to see if the promotion from Twitter can produce the effect of wanting to watch the Mencuri Raden Saleh movie to Generation Z. The research method used is quantitative, with a purposive sampling sample because there are criteria that must be met in filling out the questionnaire (Twitter users and Generation Z). and distributing questionnaires via direct message and Twitter base. This study uses data analysis including descriptive analysis, normality test, heteroscedasticity test, simple linear regression test, coefficient of determination, correlation coefficient, and t hypothesis test. Based on the results of these tests, the variable promotion of the Stealing Raden Saleh Movie on Twitter on the @mrs film account or variable X has a positive effect of 43.8% on variable Y, that is Generation Z's interest in watching. Through the results of this study, Twitter can be considered as one of the promotional media that will give certain effects to the audience. Keywords: Twitter, Promotion, Interest In Watching, Generation Z